The Power of Bromance in BL Fiction: A Homosexual Narrative in Chai Jidan’s Addicted - Su, Wenhsiang (Advances in Social Sciences Research Journal, 2019)
Male friendship has been an intriguing topic since ancient times. The relationship between two men with emotionally intense bonding or special intimacy has long been considered brotherhood. In respect of modern terminology, such friendship can be termed bromance. In human history, bromance used to be praised and documented in literature. Numerous examples can be found in both the West and the East. As time went by, bromance came to be regarded as an act of committing homosexuality. In this paper, I would like to discuss two major protagonists, Bai Luo Yin (Yin Zi) and Gu Hai, in Addicted by a Chinese female writer, Chai Jidan. This novel, also adopted for a TV drama, aroused dispute in China because of its controversial topic. As slash fiction, or so called Boys Love (BL), Addicted has triggered the issue of homosexuality since its first release. Though banned from airing on TV, the audience’s awareness of homosexuality awoke because of the admiration of the fearless love between these two protagonists. In this regard, this paper will begin with an analysis of sexuality, and then will further explain why